Psychovisual Threshold On Large Tchebichef Moment For Image Compression - Nur Azman, Abu; Ferda, Ernawan (Hikari Ltd, 2014)
JPEG standard transforms an 8×8 image pixel into a requency domain. The discontinuities of the intensity image between adjacent image blocks cause the visual artifacts due to inter-block correlations in image reconstruction. The blocking artifacts appear by the pixel intensity value discontinuities which occur along block boundaries. This research proposes the psychovisual threshold on large Tchebichef moment to minimize the blocking artifacts. The psychovisual threshold is practically the best measure for the optimal amount of frequency image signals in the image coding. The psychovisual threshold is a basic element prior to generating quantization tables in image compression. The psychovisual threshold on the large Tchebichef moments has given significant improvements in the quality of image output. The experimental results show that the smooth psychovisual threshold on the large discrete Tchebichef moment produces high quality image output and largely free of any visual artifacts.